2009
DOI: 10.1002/marc.200900177
|View full text |Cite
|
Sign up to set email alerts
|

Defined Poly[styrene‐block‐(ferrocenylmethyl methacrylate)] Diblock Copolymers via Living Anionic Polymerization

Abstract: Ferrocenylmethyl methacrylate (FMMA) is one of the very few metallocene-based monomers that are promising candidates for truly living anionic polymerization. Nevertheless, FMMA homopolymers with a narrow polydispersity, or block copolymerization studies that result in satisfying blocking efficiencies, are unknown so far. Here we describe a procedure that leads to highly regular FMMA-based polymers for the first time, characterized by polydispersity indices (PDI) of less that 1.05 and very high blocking efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
0
50
1
1
Order By: Relevance
“…THF, n‐ hexane, and LiCl were dried and deoxygenated following standard procedures. FS 1 ,34–39 FMMA 3 ,20 and vinylferrocene (VFc) 5 23 were synthesized and purified as reported elsewhere. n ‐BuLi (1.6 M solution in n ‐hexane) was used as the initiator for anionic chain growth.…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…THF, n‐ hexane, and LiCl were dried and deoxygenated following standard procedures. FS 1 ,34–39 FMMA 3 ,20 and vinylferrocene (VFc) 5 23 were synthesized and purified as reported elsewhere. n ‐BuLi (1.6 M solution in n ‐hexane) was used as the initiator for anionic chain growth.…”
Section: Experimental Partmentioning
confidence: 99%
“…All syntheses were carried out under an atmosphere of nitrogen or argon using the Schlenk technique or a glove‐box equipped with a Coldwell apparatus. Characterization methods were as reported recently20, 21, 23 and specified in the Supporting Information.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of fascinating Janus micelles by ABC block terpolymers, PS-b-PB-b-PMMA, was reported [207]. Examples of typical functional block copolymers composed of PS block(s) that have been synthesized include: PS-b-PEO, PS-b-P(2VP); PS-b-PHEMA [210]; PS-b-poly(2,3-dihydroxypropyl methacrylate) [108,109]; PS-b-poly(2-dialkylaminoethyl methacrylate) (A. Hirao and T. Watanabe, unpublished results); PS-b-poly(oligo(ethylene glycol) methacrylate) [115][116][117][118]120]; PS-b-poly(lactide) [211]; PS-b-poly(ε-caprolactone); PS-b-poly(2-(perfluorooctyl)ethyl methacrylate) [212]; PS-b-poly(6-(4-(4-methoxyphenyl)phenoxy)hexyl methacrylate) [103]; PS-b-poly(3-(trialkoxysilyl)propyl methacrylate) [113]; PS-b-poly(ferrocenylmethyl methacrylate) [102]; PS-b-poly(ferrocenyldimethylsilane) [213]; and PS-b-poly(polyhedral oligomeric silsesquioxane (POSS) methacrylate) [97]. Consequently, the hierarchy of molecular organization, passing from supramolecular assemblies to nanodevices, has been recognized as being a very important issue in nanoscience and technology.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Vancso et al [18][19][20][21] showed that PFS polymer/polymer brushes can be used as a so-called smart material in applications ranging from chemical sensors, smart membranes, to actuators. http Alternatively, the Fc moieties are tethered to the polymer backbone with a linker rather than integrated in the backbone, such as poly(vinylferrocene) (PVF) [22][23][24], poly(ferrocenylethylene) [25], and ferrocene-containing acrylates or methacrylates [26][27][28][29][30][31][32][33]. Hardy et al [34] reported the synthesis of side chain Fc-containing methacrylate polymers obtained by atom transfer radical polymerization (ATRP) and measured the thermal and redox properties of these polymers.…”
Section: Introductionmentioning
confidence: 98%